Effects of establishing cultivated grassland on soil organic carbon fractions in a degraded alpine meadow on the Tibetan Plateau ... : آثار إنشاء الأراضي العشبية المزروعة على كسور الكربون العضوي في التربة في مرج جبال الألب المتدهورة على هضبة التبت ... - Xiang Liu; Xiaotao Huang; Wenping Qin; Xiaoan Li; Zhiwen Ma; Shi Hong-xiao; Lanhai Li; Changzhong Li (OpenAlex, 2022)
The degradation of alpine meadows has induced substantial losses of soil organic carbon (SOC) on the Tibetan Plateau. A commonly-used method for rehabilitating degraded alpine meadows in this region is establishing cultivated grasslands through sowing seed mixtures, but its impact on the biochemical stability of SOC has remained inadequately explored.In this study, a total of 20 composited 0-20 cm soil samples were collected from a heavily degraded alpine meadow (DM) and three adjacent cultivated grasslands established for 3 years (CG3), 12 years (CG12), and 17 years (CG17) on the eastern Tibetan Plateau, and the SOC pool was separated into labile C pool I (LOC I), labile C pool II (LOC II), and recalcitrant C pool (ROC) in order to investigate changes in contents of SOC fractions that have different biochemical stabilities after the establishment of cultivated grassland.Although the establishment of cultivated grasslands led to increases in soil total organic C content, the increase was only significant in ... : أدى تدهور مروج جبال الألب إلى خسائر كبيرة في الكربون العضوي في التربة على هضبة التبت. تتمثل الطريقة الشائعة لإعادة تأهيل مروج جبال الألب المتدهورة في هذه المنطقة في إنشاء مراعي مزروعة من خلال زرع مخاليط البذور، ولكن تأثيرها على الاستقرار الكيميائي الحيوي لمخزون الكربون العضوي في التربة لم يتم استكشافه بشكل كافٍ. في هذه الدراسة، تم جمع ما مجموعه 20 عينة تربة مركبة من 0-20 سم من مرج جبال الألب المتدهورة بشدة (DM) وثلاث مراعي مزروعة مجاورة تم إنشاؤها لمدة 3 سنوات (CG3) و 12 عامًا (CG12) و 17 عامًا (CG17) على هضبة التبت الشرقية، وتم فصل بركة مخزون الكربون العضوي في التربة إلى بركة C القابلة للتأثر I (LOC I)، بركة C القابلة للتأثر II (LOC II)، وبركة C المتمرد (ROC) من أجل التحقيق في التغييرات في محتويات كسور مخزون الكربون العضوي في التربة التي لها ثوابتات كيميائية حيوية مختلفة بعد إنشاء الأراضي العشبية المزروعة. على الرغم من أن إنشاء الأراضي العشبية المزروعة أدى إلى زيادة في إجمالي محتوى التربة العضوي، إلا أن الزيادة كانت كبيرة فقط مع 17 عامًا من الزراعة. وجدنا أن محتويات كسور مخزون الكربون العضوي في التربة ...